Effectiveness of Beetroot (Beta vulgaris) Juice in Reducing Anemia among Pregnant Women - Ayu Dewi Nastiti Nastiti; R.A. Helda Puspitasari; Dwining Handayani; Esa Rosyda Umam; Nurul Fahmi Rizka Laily; Siti Nurhidayati (KHD Production, 2025)
Anemia in pregnancy remains a global health problem with high prevalence, particularly in developing countries, including Indonesia. Limited adherence to iron supplement consumption has prompted the need for alternative, locally available food-based interventions that are more acceptable to the community. This study aimed to evaluate the effectiveness of beetroot (Beta vulgaris) juice in increasing hemoglobin (Hb) levels and alleviating clinical symptoms of anemia among pregnant women in the Tengger region, East Java. A pre-experimental one-group pretest–posttest design was employed. Thirty-eight pregnant women in their second to third trimester who met the inclusion criteria consumed 200 ml of beetroot juice daily for 14 days. Hemoglobin levels were measured before and after the intervention using the cyanmethemoglobin method and documentation of anemia-related clinical symptoms. The findings revealed a significant increase in Hb levels from an average of 10.4 ± 0.8 g/dL to 11.5 ± 0.9 g/dL (p < 0.001). The proportion of pregnant women with mild anemia decreased from 76.3% to 34.2%, while the proportion of non-anemic status increased. In addition, clinical complaints such as weakness, dizziness, and shortness of breath were also significantly reduced. No serious adverse events were reported, with mild side effects that did not interfere with respondent compliance. In conclusion, administering beetroot juice effectively increases hemoglobin levels and improves clinical symptoms of anemia in pregnant women, and has the potential to be an affordable, non-pharmacological nutritional strategy that can support integration into antenatal programs in resource-limited settings.